Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1111/j.1365-2435.2011.01866.x
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of direct incorporation from diet and microbial amino acids to protein synthesis in Nile tilapia

Abstract: Summary 1.Further advancement in the use of stable isotope analysis in animal ecology and physiology requires a better understanding of how organisms incorporate the macromolecular elements they consume into the tissues they biosynthesize. 2. Mixing models used to infer diets from isotopic data assume that assimilated macromolecules are dissembled into elements and then reassembled in animal tissues. 3. To test this assumption, we fed Nile tilapia diets with contrasting levels of protein and in which the carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
140
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(151 citation statements)
references
References 38 publications
10
140
1
Order By: Relevance
“…However, mixing models could have overestimated the contribution of corals to their diet, precisely because of its high nutritional quality (Newsome et al 2011). Indeed, Newsome et al (2011) suggested that, for animals fed with moderate to high amounts of protein foods, mixing models can overestimate the contribution of dietary protein sources to diet, because the incorporation of dietary protein carbon was dependent on dietary protein content and on each amino acid's biosynthesis pathway.…”
Section: Resource Use By Herbivorous Fishesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, mixing models could have overestimated the contribution of corals to their diet, precisely because of its high nutritional quality (Newsome et al 2011). Indeed, Newsome et al (2011) suggested that, for animals fed with moderate to high amounts of protein foods, mixing models can overestimate the contribution of dietary protein sources to diet, because the incorporation of dietary protein carbon was dependent on dietary protein content and on each amino acid's biosynthesis pathway.…”
Section: Resource Use By Herbivorous Fishesmentioning
confidence: 99%
“…Indeed, Newsome et al (2011) suggested that, for animals fed with moderate to high amounts of protein foods, mixing models can overestimate the contribution of dietary protein sources to diet, because the incorporation of dietary protein carbon was dependent on dietary protein content and on each amino acid's biosynthesis pathway. Benthic invertebrates also presented a high nutritional quality.…”
Section: Resource Use By Herbivorous Fishesmentioning
confidence: 99%
“…Extensive tests were performed with solid AA powders to determine whether or not hydrogen atoms were exchangeable with liquid water vapor at room temperature or steam at 100°C. We used the δ 2 H of the native AA standards to calculate the δ 2 H values and the isotopic fractionation in making the derivative, similar to the method used for determining δ 13 C values of AAs (12,13). Because a subset of the hydrogen atoms is removed during derivatization, we needed to know whether the remaining hydrogen atoms had similar δ 2 H values.…”
Section: Methodsmentioning
confidence: 99%
“…These fractionations are related to biochemical pathway in autotrophs and to a combination of biochemical pathway and direct incorporation in heterotrophs. Certain AAs (e.g., glutamate, alanine) can be synthesized by any eukaryotic organism (nonessential AAs), whereas others (e.g., valine and leucine) must originate from an animal's diet (essential AAs) or gastrointestinal microbiota (13). As an animal incorporates Significance Hydrogen isotope (δ 2 H) values of bulk tissues have become valuable tracers for studying migration and movement patterns in animals, but the biochemical mechanism for how hydrogen is incorporated into heterotrophic organisms is not well understood.…”
mentioning
confidence: 99%
“…In past work, this method has produced accurate TP estimates of zooplankton (18,21), fish (17), gastropods (17), amphibians (22), and insects (19,20), ranging from simple herbivores to higher-order carnivores. Although the utility of isotopic fingerprinting has been demonstrated in both aquatic (17,21,23,24) and terrestrial ecosystems (19,20), there remains an unbridged knowledge gap between the macro-and microbiome.…”
mentioning
confidence: 99%